Optimization of the Preparation of Hydrophobic Isotactic Polypropylene Flat Sheet Membrane by Response Surface Methodology Design - Sunarti, Abd Rahman; Wan Zulaisa Amira, Wan Jusoh (ScienceDomain International, 2015)
Membrane contactor (MC) is a cost effective solution that able to reduce the release carbon dioxide into the atmosphere.The membrane applies in a MC system are highly hydrophobic, high surface porosity, low mass transfer resistance and high resistance to chemicals in the feed streams.In this study, Response Surface Methodology (RSM) design consists of 2-Level Factorial and Centre Composite Design, which were performed for screening and optimization respectively, on the production of isotactic Polypropylene (iPP) microporous flat sheet. The results obtained from the analysis of variance of contact angle, showed that the impacts of drying temperature and drying time are much more important than polymer concentration and immersion time in methanol. The most optimum membranes prepared in this experiment were membranes with the contact angle value of 106.22° by the interacting factors of dry temperature and dry time, which are 54.96°C and 18.64 minutes respectively.The regression equation obtained from the 2-Level Factorial and Membrane contactor (MC) is a cost effective solution that able to reduce the release carbon dioxide into the atmosphere.The membrane applies in a MC system are highly hydrophobic, high surface porosity, low mass transfer resistance and high resistance to chemicals in the feed streams.In this study, Response Surface Methodology (RSM) design consists of 2-Level Factorial and Centre Composite Design, which were performed for screening and optimization respectively, on the production of isotactic Polypropylene (iPP) microporous flat sheet. The results obtained from the analysis of variance of contact angle, showed that the impacts of drying temperature and drying time are much more important than polymer concentration and immersion time in methanol. The most optimum membranes prepared in this experiment were membranes with the contact angle value of 106.22° by the interacting factors of dry temperature and dry time, which are 54.96°C and 18.64 minutes respectively.The regression equation obtained from the 2-Level Factorial and Membrane contactor (MC) is a cost effective solution that able to reduce the release carbon dioxide into the atmosphere.The membrane applies in a MC system are highly hydrophobic, high surface porosity, low mass transfer resistance and high resistance to chemicals in the feed streams.In this study, Response Surface Methodology (RSM) design consists of 2-Level Factorial and Centre Composite Design, which were performed for screening and optimization respectively, on the production of isotactic Polypropylene (iPP) microporous flat sheet. The results obtained from the analysis of variance of contact angle, showed that the impacts of drying temperature and drying time are much more important than polymer concentration and immersion time in methanol. The most optimum membranes prepared in this experiment were membranes with the contact angle value of 106.22° by the interacting factors of dry temperature and dry time, which are 54.96°C and 18.64 minutes respectively.The regression equation obtained from the 2-Level Factorial and Central Composite Design can be expected to apply in the preparation of iPP membranes using diphenyl ether (DPE) diluents and can reasonably predict and optimize the performance of the iPP membranes.